Transitioning from 'outside observer' to 'inside player' in social work: practitioner and student perspectives on developing expertise in decision-making. Issue 2 (3rd April 2018) - Leonard, Kate; O'Connor, Louise
ABSTRACT: This paper reports on a six-year qualitative study of social workers' perspectives on factors influencing decision-making in children and families social work in England. Data collected between 2010 and 2016 reflect frontline practice during a period of substantial change and reform in UK social work. This paper builds on an earlier analysis with data from all three stages of the study capturing the lived experiences of practitioners ranging from student social workers to qualified advanced practitioners in management roles. Data from 9 focus groups comprising 51 participants were analysed using grounded theory. Data analysis generated four representative categories: developing agency in the social work role; troubling emotions; transitions in the development of expertise and the impact of organisational cultures in children and families social work services. An emerging theoretical framework is presented. This identifies the significance of transitions and threshold concepts in the development of the social work professional from the role of students as 'outside players looking in' through to the expertise of qualified practitioners as 'inside players' within organisations. Recognising periods of liminality, transitional learning and uncertainties in developing decision-making expertise may be of significant benefit to social work education and the profession.